Incentivizing and retaining public servants in remote areas: A discrete choice experiment with agricultural extension agents in Ethiopia - Regassa, Mekdim D.; Abate, Gashaw T.; Kubik, Zaneta (International Food Policy Research Institute, 2020)
Increased deployment of agricultural extension agents (EAs) in rural areas is grounded on their importance to spur agricultural productivity and mitigate spatial imbalances in welfare. However, the high turnover and the low motivation levels of EAs in remote areas pose challenges for equitable service provision and, in some cases, exacerbates geographic disparities. We assess the effectiveness of selected potential policy interventions to incentivize and retain EAs in remote areas of Ethiopia. To this end, we conducted a choice experiment to elicit preferences for job attributes of 761 EAs. We applied a random parameters logit model to estimate parameters of interest and to simulate the impact of possible policy interventions. The main results show that offering continuing education opportunities after two years of service increases uptake of an extension job in remote locations by 77 percentage points, which is significantly higher than the effect from doubling current salary levels (70 percentage points). EAs also expressed a strong preference for work environments with basic amenities, housing, transportation services, and wellequipped Farmer Training Centers (FTCs). Furthermore, the results from sub-sample analyses show that female EAs are less responsive to pecuniary incentives and are more concerned with the availability of infrastructure and services. Current salary levels, years of employment, and location of work are also important sources of heterogeneity in the response of EAs to potential policy changes.